ANALISIS PERAN GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM MENANAMKAN CIVIC DISPOSITION BAGI PESERTA DIDIK DI KELAS VLLL SMP NEGERI 1 TOMA - Trisnawati Laia (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
The background of this research is that education is a conscious and planned effort to create a learning atmosphere and learning process for students to actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves and society. The research objectives are 1) To find out the role of teachers in understanding civic disposition at SMP Negeri 1 Toma and 2) To find out what civic disposition is like at SMP Negeri 1 Toma. The approach used in this research is a qualitative approach and descriptive research type. The data sources in this research were the school principal as respondent, teachers, and 4 (four) students as informants. The data collection technique was carried out through stages (1) observation, (2) interviews, (3) documentation study. Data analysis was carried out through three activity streams (1) Data reduction, (2) Data presentation, (3) Drawing conclusions. Based on findings in the field, the role of teachers in schools is one of the goals of increasing learning activities in schools, with various methods carried out by a teacher, so that students are more enthusiastic about learning in school. Based on the conclusions above, the researcher suggests that. 1). The role of teachers at SMP Negeri 1 Toma should be to provide the best in the school environment so that in the future teachers will increase their sense of caring in the school environment. and 2). The civic disposition of students should be more enthusiastic about learning Civics at SMP Negeri 1 Toma, and should be further improved, because learning activities are one of the processes for training and educating students according to the curriculum implemented by the teachers in the school environment.